Insights into the profile, professional setting, and needs of in-home physiotherapists in Switzerland: a national online survey - Lauriane Rime; Chloé Schorderet; Lara Allet (BMC Health Services Research)
Abstract Background The aging of the population and the increasing prevalence of chronic diseases result in a growing number of people living with functional disabilities. Swiss public health policy and population preferences lead to an increase in the number of people staying at home rather than in institutions in Switzerland. As a result, the demand for home care services is growing and physiotherapists play a key role. In the absence of available data, this study aims to provide an overview of the profile, patients, collaborations, job satisfaction, and professional needs of in-home physiotherapists in Switzerland. Methods A cross-sectional online survey was conducted in Switzerland from December 1, 2023 to March 17, 2024. Physiotherapists practising in-home physiotherapy were eligible to participate in the survey. Swiss physiotherapy associations disseminated the survey link electronically to their members. Data were collected anonymously online using REDCap software and analysed with RStudio. A subgroup analysis was conducted between French- and German-speaking parts of Switzerland. Results A total of 439 questionnaires were analysed. Participants demonstrated a high level of professional experience, with an average of 23.5 years in the profession and 17.2% of participants exclusively practiced in-home physiotherapy. Geriatrics, orthopaedics and musculoskeletal, and neurology were the primary domains treated, with a notable patient demographic aged 80 and over. Participants most frequently collaborated with physicians, nurses, and occupational therapists. Poor ergonomics was the most prevalent encountered difficulty by participants. Overall job satisfaction was high. Participants expressed a desire to have a facilitated access to patient medical information and to improve interprofessional collaboration, and argued in favour of tariff adjustments. Conclusions This study highlights several aspects of in-home physiotherapy in Switzerland. Although physiotherapists reported a high level of overall job satisfaction, access to patients’ medical information, interprofessional collaboration and ergonomics should be enhanced. Future research should assess interprofessional collaboration effectiveness, explore patient needs, and study digitalisation’s impact on this practice.